Ghrelin Aggravates Prostate Enlargement in Rats with Testosterone-Induced Benign Prostatic Hyperplasia, Stromal Cell Proliferation, and Smooth Muscle Contraction in Human Prostate Tissues. (22nd November 2019) - Wang, Xiaolong; Wang, Yiming; Gratzke, Christian; Sterr, Christian; Yu, Qingfeng; Li, Bingsheng; Strittmatter, Frank; Herlemann, Annika; Tamalunas, Alexander; Rutz, Beata; Ciotkowska, Anna; Waidelich, Raphaela; et al.
Abstract : Epidemiologic studies revealed a context between lower urinary tract symptoms (LUTS) suggestive of benign prostatic hyperplasia (BPH) and metabolic syndrome. However, molecular mechanisms underlying this relationship are largely unknown. Prostate enlargement and increased prostate smooth muscle tone are important factors in the pathophysiology of LUTS suggestive of BPH. In the present study, we studied effects of the metabolic hormone ghrelin on prostate enlargement in rats with experimentally induced BPH, growth of cultured stromal cells from human prostate (WPMY-1), and smooth muscle contraction of human prostate tissues. Ghrelin (20 nmol/kg daily, p.o., 2 weeks) increased prostate size in rats with testosterone-induced BPH. Microarray identified 114 ghrelin-upregulated genes (2-fold or more) in these prostates, with possible roles in growth, smooth muscle contraction, or metabolism. 12 genes were selected for further analyses. In human prostate tissues, mRNA levels of 11 of them correlated positively with ghrelin receptor (GHSR) expression, but only two with the degree of BPH. Accordingly, no correlation was evident between GHSR expression level and BPH in human prostate tissues. In WPMY-1 cells, the GHRS agonist MK0677 upregulated 11 of the selected genes. MK0677 induced proliferation of WPMY-1 cells, shown by EdU assay, colony formation, proliferation markers, flow cytometry, and viability. In myographic measurements, GHSR agonists enhanced contractions of human prostate strips. Together, ghrelin may aggravate prostate enlargement, stromal cell growth, and prostate smooth muscle contraction in BPH. Ghrelin may deteriorate urethral obstruction independently from BPH, qualifying the ghrelin system as an attractive new target to be tested for LUTS treatment in BPH.